Differences in the emotional intelligence between undergraduate therapy and business students and the population norms - Gribble, Nigel; Ladyshewsky, Rick; Parsons, R. (Asia-Pacific Journal of Cooperative Education, 2017)
Students occasionally experience difficulties during work-integrated learning and clinical placements. The authors reasoned that these placement difficulties might be related to the students' emotional intelligence (EI) being underdeveloped before they commence full-time clinical placements. A cross-sectional survey design was used to measure the EI of third-year undergraduate occupational therapy, physiotherapy, speech pathology and second-year business students (n = 369). Results showed that over 40% of therapy students reported scores that are considered low or markedly low in the EI domains of independence, problem-solving and stress tolerance. The EI scores for therapy students that were significantly higher than the Australian EI norms were self-actualization, interpersonal relationships, empathy, and impulse control. The mean scores of business students were within the normal range for all EI domains. A recommendation of our study is to include strategies that develop EI throughout the therapy curriculum and when preparing students for clinical placements.